2019
DOI: 10.1039/c8ra10238d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of S–N co-doped CoFe2O4@rGO@TiO2 nanoparticles and their superior UV-Vis light photocatalytic activities

Abstract: A magnetic recoverable S–N co-doped CoFe2O4@rGO@TiO2 (CFGT-S/N) nanocomposite was synthesized via a facile vapor-thermal method. CFGT-S/N is an excellent UV-Vis photocatalyst because of the synergetic effects of S, N co-doping, the introduction of CoFe2O4 and rGO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…4(c), the calculated k app value was 2.141 min −1 , 2.417 min −1 , 2.065 min −1 , and 2.069 min −1 , for CoF, NiF, CuF, and ZnF, respectively. The kinetic rate of degradation for ferrite photocatalysts in this study was found significantly higher than those reported in the literature 32,33 . The parameters evaluated from the kinetic model, along with the linear regression value, have been displayed in Supplementary Table 3.…”
Section: Resultscontrasting
confidence: 84%
“…4(c), the calculated k app value was 2.141 min −1 , 2.417 min −1 , 2.065 min −1 , and 2.069 min −1 , for CoF, NiF, CuF, and ZnF, respectively. The kinetic rate of degradation for ferrite photocatalysts in this study was found significantly higher than those reported in the literature 32,33 . The parameters evaluated from the kinetic model, along with the linear regression value, have been displayed in Supplementary Table 3.…”
Section: Resultscontrasting
confidence: 84%
“…Moreover, the peak observed at 531.15 eV can be correlated with an oxygen vacancy, which plays a crucial role in the catalytic process as it acts as an electron trapping centre and also a substrate anchoring site. 16,35 Similar types of bands were observed for sulphur and boron-doped carbon-modied TiO 2 , with a slight shi in the peak position. For S-doped CT, the peaks located at binding energies of 530.21, 531.12 and 532.06 eV can be assigned to Ti-O, S-Ti-O and S-O bonds, respectively, indicating that some of the O atoms in TiO 2 have been replaced by S atoms.…”
Section: Chemical Composition (Xps) Analysissupporting
confidence: 67%
“…Given that the ZnO–rGO hybrid has the effect of completely degrading the dye in 40 minutes, it would appear to outperform other similar types of composite and hybrid catalysts. For example, S/N co‐doped CoFe 2 O 4 @rGO@TiO 2 NPs were able to photo‐catalytically degrade RhB in 120 min, while ZnO crystals combined with few‐layered graphene flakes reached 100 % RhB degradation in 55 min…”
Section: Resultsmentioning
confidence: 99%